A Web Service ecosystem for high-quality, cost-effective debris-flow hazard assessment. (February 2018) - Rosatti, Giorgio; Zorzi, Nadia; Zugliani, Daniel; Piffer, Stefano; Rizzi, Alessandro
Abstract: In this work, we present WEEZARD, a smart, cost-effective system, aimed at producing, managing and analysing high-quality debris-flow simulations to be used in hazard assessments. Developing the system was a challenge because of the complexity and the number of interconnected operations involved in such assessments. The goal was achieved by using a web client-server system, where a set of web services are exposed in a way similar to that used in OGC ® WPS solutions. The new system is composed of a previously developed advanced two-phase debris-flow model (TRENT2D), re-coded as a web service, and all the functionalities necessary to exploit the model, from the management of input and output (also provided as web services) to GIS features and two- and three-dimensional dynamic visualizations. Future developments include the possibility of using approaches such as the "Model as a Service" to further increase the accessibility and interoperability of the TRENT2D model. Highlights: An innovative system for debris-flow simulation and analysis has been produced. Based on a WS approach, it provides a complete environment for hazard assessment. It is composed by an advanced numerical model and a smart webGIS GUI. Respect to traditional approaches, it allows low-cost, high-quality studies.